Implementasi Hasil Konferensi Perubahan Iklim ke-26 (COP26) terhadap Pengembangan Sektor Pertambangan dan Kebijakan Lingkungan di Indonesia [The Implementation of the 26th Climate Change Conference (COP26) towards the Development of Mining Sector and Environmental Policy in Indonesia] - Then, Josephine Alessia; Pratikno, Roy Vincentius; Pattinussa, Jhon Maxwell Yosua (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2024)
The climate change crisis triggered by the greenhouse gases emission because of the usage of coal have pushed for the establishment of UNFCCC dan the COP26 meeting, where Indonesia is actively participating. This research aims to analyze the implications of the COP26 results towards the environmental policy in Indonesia, along with the opportunities and challenges faced by the mining sector in implementing those policies. Using the neoliberal theory, qualitative approach, and case study method through secondary data analysis, this research produces two main findings. First, the COP26 results are integrated into Indonesia’s environmental policy through the roadmap towards net zero emission, constructed with the International Energy Agency (IEA). This roadmap includes the early retirement plan of coal power plants, the development of renewable energy, the super grid technology, CCS/CCUS, and the conversion of electronic vehicle. Second, even though there are some significant opportunities to achieve that commitment, Indonesia also faces huge challenges, including the coal dependency, regulation that is not optimal yet, and concerns towards improper fundings.Bahasa Indonesia Abstract: Krisis perubahan iklim yang dipicu oleh emisi gas rumah kaca akibat penggunaan batu bara telah mendorong terbentuknya UNFCCC dan pertemuan COP26, di mana Indonesia turut berperan aktif. Penelitian ini bertujuan untuk menganalisis implikasi hasil COP26 terhadap kebijakan lingkungan di Indonesia, serta tantangan dan peluang yang dihadapi sektor pertambangan dalam mengimplementasikan kebijakan tersebut. Menggunakan teori neoliberalisme, pendekatan kualitatif, dan metode studi kasus melalui analisis data sekunder, penelitian ini menghasilkan dua temuan utama. Pertama, hasil COP26 diintegrasikan ke dalam kebijakan lingkungan Indonesia melalui peta jalan menuju net zero emission, yang disusun bersama International Energy Agency (IEA). Peta jalan ini mencakup rencana pensiun dini PLTU batu bara, pengembangan energi terbarukan, teknologi super grid, CCS/CCUS, dan konversi kendaraan listrik. Kedua, meskipun ada peluang signifikan untuk merealisasikan komitmen tersebut, Indonesia juga menghadapi tantangan besar, termasuk ketergantungan pada batu bara, regulasi yang belum optimal, dan kekhawatiran terkait pendanaan yang belum memadai.